(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In Kazakh national musical genre there are some problems that have not been investigated. One of these problems is used in accompaniment of musical instument. The author of this article considers a national survey on the use of terms of instruments in accompaniment of instruments and distinguishes several important aspects which are still used today. If you compare the terms «kuyi shirou»; «kuyi bastau»; «zhyr bastau», the author notes an important role for the details of instruments. The author considers the possibility of each term and in turn adds a few productive terms. By giving examples: «an shakiru»; «an bastau» and «tuindeu», A. Czubaj gives the definition of each term and he notes that the name of each tool is of great importance.